Feasibility of Hip Fracture Surgery Using a No Transfusion Protocol in Elderly Patients: A Propensity Score-Matched Cohort Study. Issue 8 (August 2017) - Yoon, Byung-Ho; Ko, Young Seung; Jang, Suk-Hwan; Ha, Jeong Ku
Abstract : Objectives: To determine whether hip fracture surgery (HFS) without transfusion affects postoperative mortality and complications in elderly patients. Design: Retrospective comparative study. Patients: Three hundred fourteen patients ≥65 years of age who underwent HFS between May 2003 and December 2014. Patients were divided into 2 groups: those who consented to blood transfusion if needed and those who did not. One-to-one propensity score matching generated 50 matched pairs of patients. Intervention: Patients underwent HFS with or without blood transfusion. In the no transfusion group, simultaneous administration of erythropoietin and iron was used as an alternative. Main Outcome Measurements: The primary outcome was postoperative mortality (90-day, 1-year, overall). The secondary outcomes were hemoglobin change and the incidence of postoperative complications. Results: HFS using a no transfusion protocol was not associated with increased mortality at any time point. Mean hemoglobin levels were significantly different between the 2 groups on postoperative day 1 (11.0 ± 1.3 vs. 10.5 ± 1.6, P = 0.002) but levels completely recovered within 2 weeks in both groups. There was also no difference in postoperative complication rates between the 2 groups, and overall hospital stays and charges were similar. Conclusions: An HFS protocol without blood transfusion was not associated with increased mortality or complications in elderly patients. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.